Implementation of Investigative Audit in the Principles of Good Corporate Governance in PT. Garuda Indonesia, Tbk (Persero) - Susanto Susanto; Elmer Micu Soriano (Universitas Ahmad Dahlan, 2023)
Introduction to the Problem: This study aims to determine the implementation of investigative audits in accordance with the principles of Good Corporate Governance (GCG) in State-Owned Enterprises (SOEs/Badan Usaha Milik Negara, BUMN) Persero in calculating state losses.Purpose/Objective Study: This study uses a statutory approach and a case approach. The case study is exemplified in the case of PT. Garuda Indonesia (Persero) Tbk (“Garuda Indonesia”). The research specification used is the explanatory legal study which aims to test a theory or hypothesis in order to strengthen or reject the existing theory or hypothesis of the research results.Design/Methodology/Approach: This is a normative juridical research, thus it is necessary to have an approach to the existing problems.Findings: According to the findings of the study, it is shown that by conducting an investigative audit based on the Good Corportate Governance (GCG) principles after the decision No. 425/Pdt.Sus.PKPU/2021/PN.Niaga.Jkt.Pst., Garuda Indonesia can improve its financial management and performance. An investigative audit that is conducted in a transparent, accountable and independent manner will increase public trust in the company and ensure that the company adopts GCG principles in managing its finances.Paper Type: Research Article